Current ideas about molecular genetic subtypes of ovarian cancer: a personalized approach and a new platform for further research - A. Rybin (Kazimierz Wielki University, 2021)
Highly malignant ovarian cancers are a histopathological diagnosis, but can be multiple diseases at the molecular level. Research aimed at identifying molecular genetic subtypes of ovarian cancer is being conducted to find an answer to the question: can different molecular subgroups influence the choice of treatment? One of the achievements of this direction is the recognition of the dualistic theory of the origin of ovarian carcinomas with their division into High-grade and Low-grade subtypes. However, the data of sequencing of the tumor genome suggest the existence of 6 subtypes of carcinoma, including two LG and four HG subtypes. Patients of subtype C1 are characterized by a high stromal response and have the lowest survival, tumors of C2 and C4 subtypes have a higher rate of intratumoral CD3 + cells, lower stroma gene expression and better survival than C1. The mesenchymal subtype C5 is widely represented by mesenchymal cells, characterized by overexpression of N-cadherins and P-cadherins, low expression of differentiation markers and lower survival than C2 and C4. The use of a consensus algorithm to determine the subtype allows the identification of only a minority of ovarian cancers (approximately 25%). In this regard, the practical significance of this classification still requires additional research, and today it is permissible to talk about the existence of only 2-3 reproducible subtypes. It is thought that it makes sense to randomize tumors into groups with altered expression of angiogenic genes and with overexpression of immune response genes, as in the angiogenic group there is a comparison of the advantage in survival (prescribing bevacizumab improves it, and in the immune group even increases bevacizumab). Molecular subtypes with poorer survival rates (proliferative and mesenchymal) also benefit most from bevacizumab treatment. The review focuses on some advances in understanding molecular, cellular, and genetic changes related to ovarian cancers with the results achieved so far in describing molecular subtypes of ovarian cancer. The available information is the basis for planning further research.